2000
DOI: 10.1177/107110070002100409
|View full text |Cite
|
Sign up to set email alerts
|

Plantarflexion Torque Following Reconstruction of Achilles Tendinosis or Rupture with Flexor Hallucis Longus Augmentation

Abstract: Nine patients treated surgically for Achilles tendon rupture (7 patients) or tendinosis (2 patients) with primary repair or debridement and augmentation with the flexor hallucis longus muscle-tendon unit were evaluated at a mean of 19 months postoperative. Subjective evaluation revealed a high level of satisfaction. All patients returned to work and only two patients reported limitation in their recreational activities. The mean post-operative AOFAS Ankle-Hindfoot Score was 90 points. Four patients reported mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
34
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 15 publications
4
34
0
7
Order By: Relevance
“…In the study of Wegrzyn et al [8] the postoperative deficit in plantar flexion torque averaged 28%, and 41% in the study of Wapner et al [4]. Interestingly, in studies where FHLT transfer was performed mainly due to the chronic Achilles tendinopathy, the deficits in plantar flexion strength have been of similar magnitude; 35% in the study of Hahn et al [5] and 28% in the study of Monroe et al [10]. Making far-reaching conclusions of the strength measurements between studies is difficult due to the small patient series, different time from operation to measurements, and large variation between patients due to their age and physical demands.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…In the study of Wegrzyn et al [8] the postoperative deficit in plantar flexion torque averaged 28%, and 41% in the study of Wapner et al [4]. Interestingly, in studies where FHLT transfer was performed mainly due to the chronic Achilles tendinopathy, the deficits in plantar flexion strength have been of similar magnitude; 35% in the study of Hahn et al [5] and 28% in the study of Monroe et al [10]. Making far-reaching conclusions of the strength measurements between studies is difficult due to the small patient series, different time from operation to measurements, and large variation between patients due to their age and physical demands.…”
Section: Discussionsupporting
confidence: 48%
“…These studies also show very low failure rates after the FHLT transfer [4][5][6][7][9][10][11][12][13].…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…In a recent study, Hahn et al found a plantar flexion peak torque deficit of 35% at 60 deg/sec in a cohort of 13 patients including ten chronic AT ruptures and three tendinopathies at an average followup of 46.5 months [9]. Two other studies in the literature included both chronic rupture and Achilles tendinosis and had some limitations [18,27]. Monroe et al also recorded a 28% peak torque deficit at 30 deg/sec [18].…”
Section: Discussionmentioning
confidence: 99%